Exploring Knowledge of Neurodisabilities and Access to Education in Custody at a Young Offender Centre in Cape Town, South Africa - Nkoana, Winnie (Department of Psychology, 2024)
Neurodisabilities are highly prevalent in the young offender population. However, there is a dearth of literature on neurodisabilities (including LDs and TBI) and access to education among young offenders in South Africa (SA). Young offenders in custody have needs across different areas, such as education, health, social and emotional. Amongst other efforts, rehabilitation approaches in prisons often include vocational training and education. The latter is especially important for youth in prison, who are still minors. Research that focuses on education for youth in custody is therefore emerging. The current study aimed to explore awareness, understanding and knowledge of neurodisabilities amongst the prison stakeholders, as well as screening tools used to screen for and identify neurodisabilities in young offenders. Furthermore, the study aimed to explore access to education in custody, by investigating how prison stakeholders make meaning of young offenders' access to education. Using qualitative semi-structured interviews, I interviewed (n=9) prison stakeholders at a youth correctional centre in Cape Town, SA. Thematic analysis, using inductive approach was the method of data analysis in the current study. The findings of the study highlight that although prison stakeholders had exposure to some neurodisabilities (e.g., LDs and FASD), they were not aware of others, such as TBI. This was largely compounded by a lack of comprehensive and validated screening tools. In keeping with previous studies prison stakeholders also reported that they are not qualified nor trained to deal with young offenders with neurodisabilities and that they are not “experts”. Although there is provision of education in custody for young offenders, there are factors that impact on their access to education in custody mainly: offender factors (high risk offenders, disruptive offenders: displaying problematic behaviors, young offenders' motivation to engage in education and presence of neurodisabilities and cognitive difficulties, which further makes it difficult for them to navigate the CJS, and systemic factors (prison overpopulation, lack of educators, attitudes of prison stakeholders and gang-related activities). The results of this study may be used to inform policy implementation in terms of rehabilitation and the use of proper screening and assessment tools to screen for various neurodisabilities in SA young offender population, as well as providing training and support for prison stakeholders, to work effectively with young offenders who may present with neurodisabilities. Additionally, the schooling structures in youth offender institutions may be reformed, to better accommodate for educational needs of young offenders, including those with neurodisabilities.